The Bildung Subject and Modernist Autobiography in An Béal Bocht (Beyond An tOileánach) - Brian Ó Conchubhair (The Parish Review, 2018)
Brian Ó Conchubhair examines An Béal Bocht as a modernist reinvention of the traditional Bildungsroman novel. By demonstrating how An Béal Bocht simultaneously plays with the conventions of the Gaeltacht Bildungsroman and deploys modernist invention, Ó Conchubhair demonstrates the importance of including An Béal Bocht in those critical conversations which laud O’Nolan’s English-language works for their literary radicality. In this context, An Béal Bocht is positioned as a text which, through a series of inversions and reinventions of the tropes of the Bildungsroman novel, sheds a ‘light on the warped nature of Irish society and cultural politics in the interwar years’ by tearing down the ideologically constructed notion of cultural identity and uncovering ‘the gap between lived reality and imagined experience.’